The Education that is built as "Especialmente Inclusiva" - Rosa Madeira (Universidade Federal de Santa Catarina, 2006)
In this article we want to approach the Special Education and the Inclusive School, as indications of the relationship of the Societies with the Difference or Differences that, in every moment of your history, these recognize and they sanction, positive or negatively.